PENGUKURAN KINERJA REKSADANA SAHAM SEBAGAI SUATU EVALUASI PORTOFOLIO INVESTOR DI PASAR MODAL MENGGUNAKAN METODE SHARPE, TREYNOR, JANSEN, M2 - Nanda Risma Wardani; Gendro Wiyono; Alfiatul Maulida (JURNAL ILMIAH EDUNOMIKA, 2021)
The aims of this study is to see the performance of equity funds measured using the Sharpe, Treynor, Jansen, and M-Square measurement methods. In addition, this study aims to see which equity funds have outperformed and underperformed the benchmark. The research period was 2016-2019. This research is a quantitative descriptive research. The result show there are 1 stock mutual funds that always perform negatively with the Sharpe method, namely Mandiri Investa Equity Dinamis mutual fund and there are no stock mutual funds that always perform positively. There is 1 stock mutual fund that always performs negatively in the observation period with treynor method, namely PNM Syariah Stock mutual fund and there is no stock mutual fund that always performs positively. Jansen method there are 2 stock mutual funds that always perform negatively, namely, M-Square Measure method there are 7 stock mutual funds that always perform positively